# algebra

posted by .

Solve the following system using the substitution method:
6x - 2y = -4
y = 3x + 2

• algebra -

sub the 2nd into the 1st:

6x - 2(3x+2) = -4
6x - 6x - 4 = -4
-4 = -4

infinite number of solutions, just use the 2nd, pick any x you feel like, and get the y
e.g.
x = 2
y = 3(2)+2 = 8
etc

What you really have is the same equation twice.
(multiply the 2nd by 2 and you will get the 1st)

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### algebra

What is the solution of the system? Solve the system of equations using the substitution method. x-y=-1 5x+4y=-23
3. ### algebra

Solve the following system using the substitution method: 3x + y = -3 y = 2x + 7
4. ### math

Solve the following system using the substitution method: y = 3x - 9 y = -x - 1
5. ### math

Solve the following system using the substitution method: 2x + 4y = 5 x = -2y + 6
6. ### Algebra

Solve the following system of equations using the substitution method:5x-7y=-18 and 4x+3y=20
7. ### Algebra 1

solve the system of equations using the substitution method. 8x-9=y, y-8x=-4